Peptic Ulcer Disease: A Comprehensive Review of Etiology, Diagnosis, and Modern Therapeutic Approaches - Akram, Muhammad; Umaru, Isaac John; Mahmood, Abid; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Ali, Jaouher Ben; Al-Musawi, Jehan Mohammed (Darul Yasin Al Sys, 2025)
Peptic ulcer disease (PUD) is an ailment of the gastrointestinal tract that is quite common and is marked by the development of open lesions known as ulcers in the stomach as well as in the proximal duodenum. It arises as a consequence of the imbalance between the protective enzymatic mechanisms of the mucosa, and the injurious agents like gastric acid, pepsin, Helicobacter pylori, and even non-steroidal anti-inflammatory drugs (NSAIDs). While many ulcers heal spontaneously, complications such as bleeding, perforation, and gastric outlet obstruction can lead to serious morbidity or mortality. With PUD, they can be treated and/or prevented if basic instruction is provided alongside a proper overview of the condition's etiological basis. In this case, pharmacological therapy and endoscopic procedures are heavily applicable.